Liverpool's Cotton Importers c. 1700 to 1914. (2nd January 2017) - Hall, Nigel
Abstract : Liverpool's first cotton importers dealt in a range of commodities and this pattern continued until the late eighteenth century. As the British cotton industry grew and new sources of raw cotton – particularly the United States – emerged, some merchants specialized increasingly in cotton in the early decades of the nineteenth century. By the end of the century, the largest importers of cotton dealt in little besides cotton. The growing prosperity of Liverpool's cotton trade drew companies from elsewhere in the United Kingdom to Liverpool to participate in this trade. By the mid nineteenth century, several key cotton importing houses had originated in the United States; by the end of the nineteenth century the largest importers there. The manner of importing cotton changed. At first, importers had to send a ship out with a captain or supercargo with broad instructions about what to freight the ship with. As communications improved, importers were able to control their purchases of cotton more closely. In the nineteenth century, a significant amount of cotton was imported through Liverpool by merchants acting on a commission basis but this form of importing declined in the later decades of the century.